Advances in the proteomic investigation of the cell secretome. (June 2012) - Brown, Kristy J; Formolo, Catherine A; Seol, Haeri; Marathi, Ramya L; Duguez, Stephanie; An, Eunkyung; Pillai, Dinesh; Nazarian, Javad; Rood, Brian R; Hathout, Yetrib
Studies of the cell secretome have greatly increased in recent years owing to improvements in proteomic platforms, mass spectrometry instrumentation and to the increased interaction between analytical chemists, biologists and clinicians. Several secretome studies have been implemented in different areas of research, leading to the generation of a valuable secretome catalogs. Secreted proteins continue to be an important source of biomarkers and therapeutic target discovery and are equally valuable in the field of microbiology. Several discoveries have been achieved in vitro using cell culture systems, ex vivo using human tissue specimens and in vivo using animal models. In this review, some of the most recent advances in secretome studies and the fields that have benefited the most from this evolving technology are highlighted.